Saf Aklın Eleştirisi’nde Şematizmin Rolü ve Önemi - SAKIZLI, SELDA SALMAN (Mustafa Çevik, 2021)
This article focuses on Transcendental Schematism in the Critique of Pure Reason. Schematism has the utmost importance for the explanation of the deduction of the categories, and application of the pure concepts to experience. As the material of sensibility and understanding are heterogeneous, schematism bears the vital role of rendering them homogeneous for the possibility of cognition. Thus, schematism both elucidates the structure of the determinate judgments and the ground of transcendental philosophy by subtly building a bridge between the sensibility and understanding. Despite its significance, schematism is often criticized for its difficulty and incomprehensibility. In this context, this study aims to illuminate the structure of schematism and underline the importance of it for transcendental philosophy as it is presented by Kant in the Critique of Pure Reason.
The Role and Importance of Schematism in the Critique of Pure Reason
Keywords: Kant; Saf Aklın Eleştirisi; Şematizm; Hayal Gücü; Sentez